An Analysis of Value-Added Taxes in Russia and Other Countries of the Former Soviet Union - Sunley, Emil (IMF Working Papers; Working Paper ;, 1995)
Since the dissolution of the Soviet Union at the end of 1991, Russia and the other countries which were members of the USSR have adopted value-added taxes. The value-added tax now provides a very significant portion of total tax revenue in all of these countries. Ideally, the value-added tax will serve as a relatively efficient, neutral, revenue source at the national level. The Russian value-added tax, however, contains a number of unique provisions, reflected in the laws of many of the other transition countries, which cause it to fall short of this standard. These countries also must decide how their value-added taxes are to apply to trade among themselves. This paper describes several of the provisions unique to the Russian value-added tax and analyzes their probable effects. It then discusses the development of arrangements which have evolved to date with respect to applying the value-added tax to trade among the transition countries, and suggests possible answers to the vexing questions raised by this issue.